PENGARUH METODE PEMBELAJARAN DARING DALAM MATERI PEMBELAJARAN IPS DI MAN 1 DELI SERDANG - Vanny, Saskia De; Samosir, Marinus Gomgom; Rahma, Enika (Cv Arsy Persada Quality, 2022)
Using technology tools, issues or information that are in progress and changes around the community and in the field of education. The purpose of education in the learning process in the primary social studies section is to make a subject of study become a good citizen of the country, able to form thinking skills, and continue the culture, especially those related to using the quality of social studies learning at the school concerned as well, namely: , learning materials, learning objectives , media explanations and behavior, hone an ability in Social Science subjects.